Business Intelligence Solution for Food Industry - Raheela Asif; Saman Hina; Sukaina Mushtaq (Journal of Basic & Applied Sciences, 2017)
Before the 1960’s organizations used to calculate figures on speculation. But ever since the demand for data analysis increased, Business Intelligence and Analytics is growing so rapidly that today it has been used for government, non-government, profitable, non profitable as well as the corporate world. The effect and impact on business intelligence system on various aspects of economy are increasing year to year. Recently, it is being used in the food industry as well. Many advanced techniques give rise to efficient methods and ways to provide a robust and effective environment for implementing BI systems in the food manufacturing industry domain; which is one of the most important industries across the globe. Hence this makes quite sense that this area would make use of such BI tools and take advantage in the similar manner as marketing firms and financial | departments for understanding their customer needs, increasing efficiency and for keeping track of the rising demands. This paper discusses a BI system on a food manufacturing industry; National Foods Canada along with the characteristics, data, methodology as well as tools used in the system. Also examples with references of the business intelligence systems used in the food manufacturing industries are presented.